Proceedings of the 46th Annual Southeast Regional Conference on XX 2008
DOI: 10.1145/1593105.1593222
|View full text |Cite
|
Sign up to set email alerts
|

Development of a graduate software project management degree

Abstract: The shortcomings of the software development industry are well documented and familiar to all computer science faculty members. Many software projects fail to deliver products with adequate functionality or are completed over budget and well past the original expected delivery date. The causes of these problems are also well documented and well known. Most often the causes of software project failure are not related to incompetency among the software developers, but inadequate skills among the project managers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The results of the current study suggested that both individual and group orientations of cohesion are important when student's projects are to be undertaken. Training in this regard will be effective as it is found that "often the causes of software project failure are not related to in competency among the software developers, but inadequate skills" of the team members [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study suggested that both individual and group orientations of cohesion are important when student's projects are to be undertaken. Training in this regard will be effective as it is found that "often the causes of software project failure are not related to in competency among the software developers, but inadequate skills" of the team members [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The education of SPM should be provided in a constructive way and through different productive teaching methods such as Active learning that based on problem base learning, experiential learning and participative learning as well as through simulations which let the students master in technical development skills before that they enter into the workforce and become professionals [6]. Due to the growing importance of SPM in the graduate and post graduate study programs, the researchers have carried out various to explore the SPME from different dimensions [7].…”
Section: Introductionmentioning
confidence: 99%